2019
DOI: 10.1186/s13104-019-4335-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased fibrinolysis-induced bradykinin formation in hereditary angioedema confirmed using stored plasma and biotechnological inhibitors

Abstract: Objective We recently investigated the pathways of immunoreactive bradykinin (iBK) formation in fresh blood of normal volunteers and of patients with hereditary angioedema due to C1-esterase inhibitor deficiency (HAE-1/-2). Herein, we adapted the techniques to small volumes (200 μl) of previously frozen citrated plasma and further analyzed the mechanisms of iBK formation with additional biotechnological inhibitors. Results Measurable iBK formation was observed under sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…While plasmin is a known activator of normal FXII ( 31 ), the kinetics was particularly intense and rapid for tPA stimulation in FXII T328K heterozygotes ( Figure 3D ). Under the same experimental conditions, the plasma of HAE-C1-INH patients also released iBK faster than the controls in response to tPA, but the concentration did not exceed 300 ng/ml ( 21 ), whereas values in the HAE-FXII group were larger after 10 or 20 min of incubation ( Figure 3D ). The exhaustion of iBK formation later in the 2 h incubation period is specific to HAE-FXII plasma, suggesting the consumption of a factor critical for kinin production.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…While plasmin is a known activator of normal FXII ( 31 ), the kinetics was particularly intense and rapid for tPA stimulation in FXII T328K heterozygotes ( Figure 3D ). Under the same experimental conditions, the plasma of HAE-C1-INH patients also released iBK faster than the controls in response to tPA, but the concentration did not exceed 300 ng/ml ( 21 ), whereas values in the HAE-FXII group were larger after 10 or 20 min of incubation ( Figure 3D ). The exhaustion of iBK formation later in the 2 h incubation period is specific to HAE-FXII plasma, suggesting the consumption of a factor critical for kinin production.…”
Section: Resultsmentioning
confidence: 85%
“…We previously reported that iBK formation was negligible in either whole blood or plasma incubated at 37°C without stimulus both in healthy donors and HAE patients sampled during remission (HAE-C1-INH type I or II) ( 20 , 21 ). This may be paradoxical because HK is spontaneously and progressively cleaved in the blood of patients with HAE-C1-INH ( 15 , 16 ) or HAE-nC1-INH ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations